Tilbage til kilderne: Om at genopdage en bronzealderlig offertradition - Frost, Lise; Refshauge Beck, Malene (Kuml, 2025)
Returning to the sources A Bronze Age depositional tradition rediscovered Interest in the use of metal detectors has grown markedly in recent years, and one consequence of this is reflected in the increasing number of records of Bronze Age depositions. At both Moesgaard Museum and Østfyns Museer, metal-detector finds have prompted the undertaking of archaeological excavations, which have demonstrated that the objects were deposited at springs. Conventionally, nuances in the specific relationship between Bronze Age depositions and landscape at the deposition locality have often been concealed by the generic terms employed for these depositions, i.e. field/bog finds. There are records of offerings at springs all across Europe and throughout most of prehistory. But these finds associated with water flowing out of the ground, which may even have dried up in modern times, are difficult to recognise without an archaeological excavation. Such investigations have only rarely been conducted because most Bronze Age depositions have been found accidentally, during agricultural cultivation, peat digging etc. As part of a KFU (Kulturministeriets Forskningsfond)-financed research project, based on the results of excavations, topographical maps and examinations of old records in the archaeological literature and in museum archives, we are nevertheless able to conclude that depositions at springs constitute a previously under-illuminated element of the Bronze Age wetland finds group. More than a century ago, the famous well offering at Budsene was published and the original article mentions other finds from springs at Kirke Søby and Roskilde (figs. 1-3), but spring offerings are only rarely mentioned subsequently in the literature. This article presents 30 examples of finds from the Danish Bronze Age that, based on archival information and topography, are considered to derive from springs (figs. 4-7, tab. 1). The period IV sword found by a metal detectorist in 2012 at Stærkær near the river Gudenåen prompted an archaeological excavation conducted by Moesgaard Museum. Although it was not possible to relate the sword to a specific layer, the Stærkær excavation is a rare example of a documented, direct link between the deposited object and a spring-fed pond on the edge of a hill (figs. 8-14). An even closer link between a deposition and a spring has been demonstrated at Hedegyden, near Nyborg, where Østfyns Museer undertook an excavation of an ornament deposition found by metal detectorists, which is dated to period V of the Bronze Age. The Hedegyden find is a multi-type deposition, consisting of three hanging vessels, a belt ornament and three lumps of metal. Remains of a wooden lid or container in one of the hanging vessels, as well as fragments of bark and wood, had also been deposited. Water still flowed at the site, and pale-yellow sand, together with pollen and NPP (non pollen)-analysis, supported the spring interpretation. The NPP-analysis indicated the presence of bee hairs, which suggests that honey or beeswax were included in the deposition. The sequence of the deposition can be placed in a ‘chaîne opératoire’ (figs. 15-18). In addition to the relatively detailed insight into the offering act itself, depositions at springs make a valuable and more general contribution to improving our understanding of the use by Bronze Age communities of the landscape outside settlements and fields.